Pengaruh Karakteristik Kepemimpinan Yosua bagi Kepemimpinan Kristen di Era Modern - Wenas, Joshua Christian (Sekolah Tinggi Teologia Kerusso Indonesia, 2020)
The topic of leadership becomes increasingly important because people are increasingly talking about and fighting over it as a determinant factor of the success of a job. Leadership plays an important role in determining the advance or setback of an organization or group. Joshua can be used as a figure in today's leadership. Speaking of character, Joshua is a very consistent person. This fact can be seen when Joshua became a servant of Moses. His life shows an example of great loyalty, obedience, commitment, determination, communicative and a strong faith. The incident of sending spies to the land of Canaan, Joshua and Caleb were not only determined to do what was assigned, but the determination that was in them was also shown in concrete actions. This event showed when the tasks and responsibilities are completed, the ten spies from the ten tribes of Israel gave exaggerated report about the condition of the land of Canaan and displayed pessimism and an exaggerated impression on the Israelites.